Clinical use of pregabalin in the management of central neuropathic pain - Nanna B Finnerup (Dove Medical Press, 2007)
Nanna B Finnerup, Troels S JensenDanish Pain Research Center, Department of Neurology, Aarhus University Hospital, Aarhus, DenmarkAbstract: Central neuropathic pain (central pain) is treated with antidepressants, various anticonvulsants, opioids, and cannabinoids, but in many cases treatment is insufficient and associated with a range of side-effects. This review addresses a new treatment for neuropathic pain, the anticonvulsant pregabalin. We review the pharmacology, mode of action, pharmacokinetics, and safety of pregabalin as well as two randomized efficacy studies in central pain and a brief overview of efficacy in peripheral neuropathic pain. Pregabalin appears to have efficacy in treating central pain comparable to that in peripheral neuropathic pain as well as efficacy of other recommended drugs for central pain. Pregabalin also improves disturbed sleep and anxiety. Pregabalin is well tolerated; the most common side-effects are somnolence, dizziness, ataxia, and weight gain. Pregabalin is suitable for patients on multiple drugs although there may be additive CNS-related side-effects. Thus, pregabalin has a primary role in central pain patients.Keywords: central pain, neuropathic pain, pregabalin, pharmacology